The comparative value of Greenleaf sudangrass and common sudangrass as pasture for fattening spring pigs. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment was conducted in the summer of 1955 with spring pigs on pasture. Its object was Ito compare the quality of the two varieties of sudangrass. Two lots were fed shelled corn and a mixed animal and plant protein supplement made of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. Both were self-fed, free choice. Lot 1 was pastured on Greenleaf sudangrass; Lot 2 on Common sudangrass.
Keywords: Swine; Greenleaf sudangrass; Common sudangrass; Gain